OXIDE CERAMICS: THE ROLE OF SURFACE AND GRAIN BOUNDARIES FOR RELIABLE FUNCTIONAL APPLICATIONS - Varela, Jose Arana [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Santos Muccillo, Eliana Navarro dos; Muccillo, Reginaldo; Ohji, T.; Singh, M. (Wiley-Blackwell, 2016)
Oxide ceramics find large application in several segments of the human life, as functional materials are used as components in several devices such as sensors of chemical species for improved environment, surge protectors for electronic appliances, and electrochemical transducers for sustainable alternative energy production. Other applications involve detectors in medical appliances, components of mobiles and computers, etc. One of the most important features deals with the electrical behavior of the oxide ceramics, which span from superconductors to insulators, including ionic/electronic/mixed conductors and semiconductors. This chapter reports a brief overview of ceramic oxide semiconductors and ionic conductors, taking into account the role of surfaces and interfaces (mainly grain boundaries) on their performance as components in surge protectors-varistors, in chemical sensors and solid electrolytes in solid oxide fuel cells.
Keywords: oxides; grain boundaries; varistors; chemical sensors; solid oxide fuel cells